Confluence between forest ecosystems and scientific knowledge against climate change: Peruvian legal framework - Rodríguez Mirano, Jeanpierre; Vértiz-Osores, Jacinto Joaquín (Nexo Revista Científica, 2021)
This article consists of an exploratory study that reflects on the scope of climate change policies in Peru, the generation of scientific knowledge from the study of forest ecosystems and the feasibility of a scenario of confluence between both. It was based on a qualitative analysis, through the design of Emergent Founded Theory, of a juridical-comparative type. The value of the vulnerability of a forest ecosystem as a policy analysis tool for adaptation to climate change was explained, in addition to the instantaneous benefits resulting from the systematization of scientific information to facilitate the process of defining strategies towards these policies.